Proceedings of the 5th International Workshop on Web-Scale Knowledge Representation Retrieval &Amp; Reasoning 2014
DOI: 10.1145/2663792.2663798
|View full text |Cite
|
Sign up to set email alerts
|

Structure Learning of Bayesian Network with Latent Variables by Weight-Induced Refinement

Abstract: Bayesian network (BN) with latent variables (LVs) provides a concise and straightforward framework for representing and inferring uncertain knowledge with unobservable variables or with regard to missing data. To learn the BN with LVs consistently with the realistic situations, we propose the information theory based concept of existence weight and incorporate it into the clique-based learning method. In line with the challenges when learning BN with LVs, we focus on determining the number of LVs, and determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We defined a causal intensity indicator and found that the causal intensity of two points with direct causality is significantly greater than the causal intensity of two points that are jointly affected by the hidden variables and do not have direct causality. The causal intensity [19] is denoted as:…”
Section: Stage 3: Causal Intensitymentioning
confidence: 99%
“…We defined a causal intensity indicator and found that the causal intensity of two points with direct causality is significantly greater than the causal intensity of two points that are jointly affected by the hidden variables and do not have direct causality. The causal intensity [19] is denoted as:…”
Section: Stage 3: Causal Intensitymentioning
confidence: 99%
“…In [4], the authors investigate on ontology matching based on learning using partially labeled data, while [5] presents a structure learning algorithm for uncertain knowledge representation and inference.…”
Section: Research Papersmentioning
confidence: 99%